Design and implementation of perfluoroelastomer (PFE) raw material cutting jig using 3D printing to improve valve cluster production efficiency at PT XYZ - Yuselin, Nensi; Abiyyu, Muhammad Rafli (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2026)
The raw material cutting process of is a crucial stage in the production of valve clusters at PT XYZ. The manual cutting method currently in use has several constraints, including inconsistent cut results, relatively long cutting times (an average of 28.2 seconds per cut), and the potential for defects due to non-uniform thickness. This research aims to improve the efficiency of the PFE cutting process and identify the optimal cutting process time by designing and implementing cutting jigs using 3D Printing technology. The DMAIC (Define, Measure, Analyze, Improve, Control) methodology is used as a research framework. In the Define stage, the main problems are identified namely inconsistencies in the cut results, high cycle times, and often production targets that are not achieved due to rejection. Data at the Measure stage shows that the manual cutting time by two operators is on average 28.2 seconds per cut. The analysis at the Analyze stage using fishbone diagrams identified the root of the problem from manual cutting methods, untrained operators, and the use of blunt razors. Based on the root of the problem found, at the Improve stage, a PFE cutting jig was designed using 3D Printing as a solution. The implementation of this jig has successfully lowered the average cutting time per piece of PFE to 24.55 seconds, compared to the manual method which averaged 28.2 seconds. This jig is expected to improve the consistency of the cut result and significantly reduce the cutting cycle time.